Pengembangan Media Pembelajaran Flashcard pada Tema Energi dan Perubahannya Kelas III SD - Ependi, Yapan; Misdalina, Misdalina; Hera, Treny (Indonesian Research Journal on Education, 2022)
This research uses Research and Development (R&D) research methodology. Research and development methods are used to produce certain products and test the validity, practicality and effectiveness of these products by being tested on 20 third grade students. The product produced in this research is Flashcard learning media. Flashcard learning media is carried out based on the ADDIE development steps (Analysis, Design, Development, Implementation, and Evaluation). The purpose of this research is toproduce a product for developing Flashcard learning media on the theme of Energy and Its Changes for class III SD that is valid, practical, and effective. The results showed that the development of Flashcard learning media on the theme of Energy and Its Changes for class III SD carried out by researchers had been developed with valid categories from the validation sheet of Indonesian language, PPKn and Mathematics material experts, teacher material validation, media experts, student response questionnaires and pretest results. and posttest with gain-score. The results of the analysis on material expert validation were 95.24%, 84.52% very feasible, teacher material validation 97.62% very feasible,media experts 92.5% very feasible. Questionnaire responses of 97.94% students were very practical, and the average results of the pretest were 66%, the posttest was 81.5% and the gain-score was moderate. This shows that the development of Flashcard learning media on the theme of Energy and Change is effective.